CHARACTERISTICS OF SENSORY AND MICROBIOLOGY QUALITY OF REBON SHRIMP PASTE (Acetes sp.) MADE USING BACKSLOPPING FERMENTATION METHODS - Damayani, Noventa Dwi; Hasan, Bustari; Iriani, Dian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractThis study aims to evaluate the characteristics of the sensory quality, pH, ALT and BAL of cincalok made by the backslopping fermentation method with different inoculums. The method used was an experimental method with Racangan Acak Lengkap (RAL). The treatment given consisted of adding inoculums of 0% (C0), 10% (C10), 15% (C15), and 20% (C20). This study consisted of 2 stages, namely 1) Preparation of the inoculum, 2) Preparation of the cincalok using the backslopping method. The parameters tested were sensory quality test, lactic acid bacteria test, total plate count test, pH. he results showed that the calculation of the pH of the cincalok produced with different inoculum treatments had different amounts as follows: C03.87%, C104.53%, C154.27 and C204.03%. The optimal fermentation time to obtain the inoculum is C0(control), which is 3.87, and the addition of 20% inoculum is 4.03. The best treatment is the addition of 20% inoculum with quality characteristics of visual value obtained attractive results and neutral pink color, The quality of the taste value obtained the results of the fresh sour and salty cincalok, the quality of the aroma value obtained the result of the fermented fresh sour aroma of cincalok, the quality of the texture value obtained the result of a very dense texture, slightly chewy and a little bit watery. The pH for the addition of 20% inoculum with 3 days of fermentation time was 4.85, the calculation of the ALT value for the addition of 20% inoculum resulted in 8.9 x 104(colony / g), and the calculation of the best BAL value for the addition of 20% inoculum was 2.60 x 104. Keywords: Rebon shrimp, Cincalok, Backslopping